Development of Optical Biosensor for the Detection of Pesticides - Singh, Gurpreet (My University, 2014)
An optical biosensor was designed for determination of Pesticides and herbicides . Detection was obtained with immobilised Chlorella vulgaris microalgae entrapped by Ca-alginate and in free state. Effects of pH, algal density, substrate concentration, inhibition of alkaline phosphatase by organophosphate pesticides like acephate, chlorpyrifos, triazophos and malathion and herbicides like atrazine, metribuzin and glyphosate were studied. Detection limit for herbicides like atrazine, metribuzin, glyphosate was found to be in free state 10-10 M, 10-8 M, 10-6 M and in immobilized state 10-10 M, 10-9 M, 10-7 M respectively. Detection limit for organophosphorus pesticides like acephate, chlorpyrifos, triazophos was found to be in free state 10-8 M, 10-7 M, 10-6 M and in immobilized state 10-9 M, 10-7 M, 10-7 M respectively. Malathion did not inhibit the alkaline phosphatase detected by this optical biosensor.
MS, SCBC
Keywords: optical biosensor; pesticides; herbicides; chlorella vulgaris